2015
DOI: 10.1111/1750-3841.13124
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Oxidation in Fish and Fish Products

Abstract: Fish and fish products are important from a nutritional point of view due to the presence of high biological value proteins and the high content of polyunsaturated fatty acids, especially those of the n-3 series, and above all eicosapentaenoic acid and docosahexaenoic acid. However, these important food products also contain significant amounts of cholesterol. Although cholesterol participates in essential functions in the human body, it is unstable, especially in the presence of light, oxygen, radiation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 107 publications
0
23
0
Order By: Relevance
“…Fish and fish products Fish are noted for their high levels of polyunsaturated fatty acids of the omega-3 series, such as eicosapentaenoic acids (EPA, C20: 5) and docosahexaenoic acids (DHA, C22: 6), which are compounds directly related to health benefits (Calder, 2015;Haimeur Raatz, Silverstein, Jahns, & Picklo, 2013;Zheng, Hu, Zhao, Yang, & Li, 2013). However, the lipid fraction of fish, which is composed mainly of PUFAs and with high levels of cholesterol, is particularly susceptible to oxidation processes when exposed to favorable factors during processing and storage (Dantas et al, 2015;Freitas et al, 2015;Márquez-Ruiz & Morales, 2015;Saldanha et al, 2008). In addition, the presence of pigments, such as myoglobin and hemoglobin, and traces of metal ions in fish makes this food matrix more susceptible to oxidation.…”
Section: Use Of Natural Antioxidants In the Prevention Of Cholesterolmentioning
confidence: 99%
See 1 more Smart Citation
“…Fish and fish products Fish are noted for their high levels of polyunsaturated fatty acids of the omega-3 series, such as eicosapentaenoic acids (EPA, C20: 5) and docosahexaenoic acids (DHA, C22: 6), which are compounds directly related to health benefits (Calder, 2015;Haimeur Raatz, Silverstein, Jahns, & Picklo, 2013;Zheng, Hu, Zhao, Yang, & Li, 2013). However, the lipid fraction of fish, which is composed mainly of PUFAs and with high levels of cholesterol, is particularly susceptible to oxidation processes when exposed to favorable factors during processing and storage (Dantas et al, 2015;Freitas et al, 2015;Márquez-Ruiz & Morales, 2015;Saldanha et al, 2008). In addition, the presence of pigments, such as myoglobin and hemoglobin, and traces of metal ions in fish makes this food matrix more susceptible to oxidation.…”
Section: Use Of Natural Antioxidants In the Prevention Of Cholesterolmentioning
confidence: 99%
“…The most common COPs present in foods are 7‐ketocholesterol, 20α‐hydroxycholesterol, 25‐hydroxycholesterol, α, β‐epoxycholesterol and 7α, 7β‐hydroxycholesterol (Hur et al., ; Orczewska‐Dudek et al., ). The profile of the products formed and their concentrations are influenced by factors such as water activity, oxidation time, pH, exposure to light and irradiation, elevated temperatures, physical state of cholesterol, and food composition (presence of unsaturated fatty acids) (Barnaba, Rodríguez‐Estrada, Lercker, García, & Medina‐Meza, ; Dantas et al., ; Medina‐Meza & Barnaba, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, some authors have demonstrated that sardines also contain high levels of cholesterol (Saldanha and others ; Scherr and others ). These 2 types of compounds, n ‐3 PUFAs and cholesterol, are not chemically stable and this instability is influenced by their chemical structure, the presence of oxygen, light, metal ions, and the processing techniques (heat) used, among other factors (Dantas and others ; Barriuso and others ).…”
Section: Introductionmentioning
confidence: 99%
“…The temperature used and the time required to prepare fish and fish products are perhaps the main factors that contribute to the degradation of cholesterol, forming cholesterol oxidation products (COPs) (Dantas and others ; Leal‐Castañeda and others ). These substances are structurally similar to cholesterol and are normally present in small quantities formed by endogenous metabolic processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation